ChemInform Abstract: Direct Arylation of Aromatic C—H Bond Catalyzed by Phthalocyanine. Issue 15 (April 2015) - Gai, Lizhi; To, Ching Tat; Chan, Kin Shing
Abstract: The direct C—H arylation with aryl iodides provides the corresponding biaryls.